Analisis Fail Path Pada Arsitektur Software Defined Network Menggunakan Dijkstra Algorithm - Eka Putri Aprilianingsih; Rakhmadhany Primananda; Aswin Suharsono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Software Defined Network is a new concept that is used to fix traditional network's issues by making the separation between the control plane and the data plane in many different network devices vendor. The communication between control plane and data plane use the OpenFlow Protocol. SDN has some abilitiesin many network technology methods, and has been widely implemented such as network routing. There are some problems in routing, for example is file path. When there is a fail path arises, the system will look for another shortest paths by using Dijkstra Dlgorithm. Dijkstra Algorithm will be implemented using SDN then will be analyzed. Implementation uses a mesh topology and Pyretic as the controller. Then algorithms will be tested with 3 scenarios. In these scenarios, there are 4 tests: the testing topology, throughput, latency and convergence. Tests conducted topology to generate the shortest path. Scenario 1, is h1, h4, h3, h7 with cost 10. Scenario 2, is h1, h2, h3, h7 with cost 13. Scenario 3, is h1, h4, h6, h7 with cost 18. The purpose of throughput testing is to count packets arrive at the destination side. Scenario 1 had maximum throughput at 12.0 Gbits / sec. Scenario 2 is 9.56 Gbits / sec. Scenario 3 is 9.68 Gbits / sec. Latency test is to calculate the time taken from a package to its destination. Scenario 1 produced the highest latency at 0.162ms. Scenario 2 is 0.190ms. Scenario 3 is 0.150ms. Convergence test is to determine the changes in the time required when fail path. Scenario 1 has no file path so there were no results in convergence. Scenario 2 is 2.009ms. Scenario 3 is 3.01ms.